Instrument for Measuring the Character of Pancasila Student Profile in Junior High School - Aprila, Ana; Gading, I Ketut; Lestari, Luh Putu Sri; Dantes, Nyoman; Suarni, Ni Ketut (Bisma The Journal of Counseling, 2024)
The Pancasila Student Profile is the main goal in developing student character. However, observations in the field show that observations on the character of the Pancasila Student profile are still limited. Therefore, an appropriate assessment instrument is needed for Counseling Guidance (BK) teachers and subject teachers to assess the character of Pancasila Students. This study aims to describe the design of the instrument, analyze and describe the validity of the content and validity of the construction, and describe the reliability of the Pancasila Student character measurement instrument. This Research and Development (R&D) uses a 10-step research design for the development of Dantes instruments. The trial subjects were 300 students from 9 junior high schools. Data collection was carried out by involving 5 postgraduate BK lecturers at Ganesha Education University and 2 senior BK teachers as judges. Data analysis using content validity analysis with the result of content validity index (CVI) = 0.95, indicating a special category. The analysis of construct validity using the Rotated Component Matrix shows 24 indicators with a loading factor value of > 0.30, which forms a consistent and feasible factor. The results of this research are expected to encourage further research and become a relevant educational document, serving as a reference for innovative counseling service materials and strategies in helping student development. This study shows that the instrument developed is effective in measuring the character of Pancasila students and has the potential to be implemented more widely.